2014
DOI: 10.1073/pnas.1320401111
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte activation is suppressed in both normal and injured brain by FGF signaling

Abstract: In the brain, astrocytes are multifunctional cells that react to insults and contain damage. However, excessive or sustained reactive astrocytes can be deleterious to functional recovery or contribute to chronic inflammation and neuronal dysfunction. Therefore, astrocyte activation in response to damage is likely to be tightly regulated. Although factors that activate astrocytes have been identified, whether factors also exist that maintain astrocytes as nonreactive or reestablish their nonreactive state after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
113
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(132 citation statements)
references
References 53 publications
10
113
0
Order By: Relevance
“…However, FGF-2 also inhibited the TGF-␤1-mediated increase of GFAP expression in astrocytes (44). A recent study demonstrated that the loss of the FGF-2 receptor in astrocytes induced astrocyte activation in unperturbed mice, suggesting that FGF signaling in astrocytes is required to maintain their nonreactive state (36). In this study, we have confirmed the activated effects of neurons on astrocyte and the related signaling (supplemental Fig.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, FGF-2 also inhibited the TGF-␤1-mediated increase of GFAP expression in astrocytes (44). A recent study demonstrated that the loss of the FGF-2 receptor in astrocytes induced astrocyte activation in unperturbed mice, suggesting that FGF signaling in astrocytes is required to maintain their nonreactive state (36). In this study, we have confirmed the activated effects of neurons on astrocyte and the related signaling (supplemental Fig.…”
Section: Discussionsupporting
confidence: 82%
“…This study has revealed that the inactivation of mTORC1 in postmitotic neurons causes moderate reactive astrogliosis. The loss of neural mTORC1 activity may induce astrogliosis by reducing the neuronal secretion of FGF-2, thereby inhibiting FGF receptor signaling in astrocytes, which is required to maintain their nonreactive state (36) (Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a proof of principal, we also investigated if additional molecules could revert A1s to a non-reactive phenotype. We tested the anti-inflammatory cytokine TGFβ and FGF (as it has been previously shown that astrocyte activation is suppressed in the injured brain by FGF signaling 19 ). We grew A1s in culture, then treated with TGFβ or FGF and found both significantly decreased reactive astrocyte transcript levels (Fig.…”
Section: Reactive Microglia Induce A1 Reactive Astrocytes By Secrementioning
confidence: 99%
“…Transfection of tyrosine kinase-deleted FGFR1 into rat SN has been shown to significantly reduce the number of dopaminergic neurons in SN and the dopamine level in striatum [15]. Moreover, it has recently been reported that FGF signaling is required for astrocytes to maintain their nonreactive state under physiological conditions and suppress their activation after injury [16]. Accordingly, the downstream intracellular signaling pathways of FGFRs are also diverse, including Ras/mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinase 1/2 (ERK1/2), phosphatidylinositol 3-kinase (PI3K)/AKT, and phospholipase Cγ (PLCγ) [17].…”
Section: Introductionmentioning
confidence: 99%